Systemic inflammatory regulators and risk of acute-on-chronic liver failure: A bidirectional mendelian-randomization study - Wang, Shengnan; Zhu, Hao; Pan, Lin; Zhang, Mengyuan; Wan, Xiaoqiang; Xu, Hongqin; Hua, Rui; Zhu, Mingqin; Gao, Pujun (Frontiers in Cell and Developmental Biology, 2023)
Inflammation plays a role in the pathogenesis of acute‑on‑chronic liver failure (ACLF), however, whether there is a causal relationship between inflammation and ACLF remains unclear. A two-sample Mendelian randomization (MR) approach was used to investigate the causal relationship between systemic inflammatory regulators and ACLF. The study analyzed 41 cytokines and growth factors from 8293 individuals extracted from a genome-wide association study (GWAS) meta-analysis database involving 253 ACLF cases and 456095 controls. Our results showed that lower stem cell factor (SCF) levels, lower basic fibroblast growth factor (bFGF) levels and higher Interleukin-13 (IL-13) levels were associated with an increased risk of ACLF (OR = 0.486, 95% CI = 0.264 – 0.892, P = 0.020; OR = 0.323, 95% CI = 0.107 – 0.972, P = 0.044; OR = 1.492, 95% CI = 1.111 – 2.004, P = 0.008, respectively). In addition, genetically predicted ACLF did not affect the expression of systemic inflammatory regulators. Our results indicate that cytokines play a crucial role in the pathogenesis of ACLF. Further studies are needed to determine whether these biomarkers can be used to prevent and treat ACLF.